Research Trends On Pests of Manganji Chili Plants(Capsicum Annuum L): A Bibliometrix Review - Revandi Putri, Alicia; Panayungan, Elang; Saleh, Ismail; March Syahadat, Ray (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
Manganji chili is a distinctive horticultural commodity from Japan with high economic value; however, the greatest challenge in its production lies in pest infestations. This study aims to analyze research trends concerning pests affecting Manganji chili plants (Capsicum annuum L.). The analysis was conducted using a bibliometric approach based on Scopus data, supported by VOSviewer and Bibliometrix tools. The primary focus was directed at five key pests: Aphis gossypii, Scirtothrips dorsalis, Nezara viridula, Spodoptera litura, and Filicaulis bleekeri. Results indicate that although the number of publications remains limited and inconsistent annually, there has been an upward trend over the past two decades, particularly in Japan, the country of origin of Manganji chili. The identification of keywords, topic clusters, and prolific authors revealed a dominant research focus on biological control and banker plant systems. This study identifies research gaps that can be leveraged to develop more effective and sustainable pest control strategies. Therefore, the findings are expected to serve as a foundation for future research and policy-making in the management of Manganji chili pests.